Investor Psychology and Stock Market Dynamics : A Systematic TCCM Review and Future Pathways - G., Yadhukrishnan; R., Priya (Indian Journal of Research in Capital Markets, 2025)
Purpose : The purpose of this study was to review the current literature on investor psychology and its impact on the dynamics of the stock market. Although there has been growing academic interest in the field, no comprehensive review has yet addressed the psychological aspects of market behavior across different contexts. Methodology : The SPAR-4-SLR protocol was used to conduct a systematic literature review of studies indexed in the Scopus database since 2000. The theory, context, characteristics, and methodology (TCCM) framework was adopted for structuring the review of the literature. Findings : The review showed that the theory of behavioral finance and its constructs, such as overconfidence, herding, and sentiment, were prevalent in the domain, and the regression-based models were the most commonly used approach. The focus was disproportionately on developed markets like the United States, and emerging markets and other contexts, such as cryptocurrency and ESG investing, were underrepresented. Implications : It is recommended that future studies need to embrace newer psychological theories like cognitive dissonance, social comparison, etc., cross-cultural and high-frequency data analysis, and more sophisticated methods like machine learning, experimental designs, and causal inference approaches to increase empirical robustness and relevance. Originality : Current literature has a significant gap in terms of a complete synthesis of investor psychology in the wider context of stock market dynamics.